Emotional Intersectionality in pre-service teacher's identity and education during times of crises - Finardi, Kyria; Diniz de Figueiredo, Eduardo (Estudos Linguísticos e Literários, 2025)
In this study, we analyze the emotions revealed in the recollective reflection of a teacher educator in charge of the English Language Practicum course during emergency remote teaching. Because of the impossibility to take the pre-service teachers to schools for their practicum, the teacher educator decided to pair her group with other similar courses abroad through virtual exchange. Our analysis suggests that anxiety associated with speaking English with other international students/teachers and/or native speakers coupled with the anxiety associated with the need to deal with technology during the virtual exchanges intersected creating mixed feelings in all involved. Data analysis also suggests the need to identify, interrogate and interrupt colonial views of language proficiency associated with a certain native speaker in language teacher education.